Bacteriological investigation of pop-eye disease in marine ornamental aquaria fishes from Andaman - Shome, Rajeshwari; Shome, B R; Krishnamurthy, V; Dey, S C; Soundararajan, R (Indian Journal of Fisheries, 2011)
The ornamental marine aquarium fishes suffering from eye disease with symptoms of cataract, exophthalmia, anorexia, dullness and death occurring in 3-5 days were investigated for etiological agent and control measures. The prominent fish species affected were grouper (Epinephelus spp.), Caranx spp., Triacanthus spp., bat fish iPlatax spp.), undulata trigger fish (Balistrapus undulatus), lion fish (.Pterins spp.), vagabond butterfly fish (Chaetndon vagabundus), pearl toby (Canthigastur margaritata), tang fish (Naso spp.) and snapper (Lutjanus spp,). No parasites were found to be involved in infected eyes on macroscopic examination. Out of 19 representative isolates selected for detailed bacteriological analysis fifteen, three and one isolates were Vibrio parahaemolyticus. Vibrio anguillarum and Aeromonas salmonicida respectively. The in-vitro antibiotic sensitivity test showed multiple drug resistance against a minimum of five antibiotics to a maximum of thirteen antibiotics. However, norfloxacin and chloramphenicol were found to be effective against all the bacterial isolates. In isolation, treatment with chloramphenicol @ 50 mg kg"’ body weight when introduced intramuscularly for 5 days was able to cure the disease. As the disease was cured by antibiotics, no parasites could be found on macroscopic examination and 18 out of 19 isolates were found to belong to the genus Vibrio.